Is coronary sinus blood oxygen tension behavior determined by myocardial oxygen tension variation during cardiac reperfusion? - Cicogna, A. C.; Ferreira Tucci, P. J.; Spadaro, J.; Marchesan Rodrigues, M. A.; Curi, P. R.; Lucchiari, P. H. (International Heart Journal (Japanese Heart Journal), 1988)
The relationship between coronary sinus blood oxygen tension (CSPO 2) and myocardial oxygen tension (MPO 2) variations during cardiac ischemia and reperfusion was studied in anesthetized open-chest dogs. Oxygen tension was measured by a polarographic method. Ischemia resulted in a slightly decreased CSPO 2 and a more pronounced reduction of MPO 2. After reperfusion the CSPO 2 rose rapidly and transiently before it returned gradually to the control level. By contrast, during the recovery period, the MPO 2 increased slowly, with recovery occurring long after the peak of CSPO 2. These data suggest that during the reperfusion phase, the CSPO 2 variation is probably due to opening of the myocardial arteriovenous shunts instead of an increase of flow through the myocardial capillary bed.
Keywords: animal experiment; blood oxygen tension; coronary sinus; dog; heart muscle ischemia; heart muscle oxygen consumption; heart muscle reperfusion; nonhuman; priority journal; Animal; Coronary Circulation; Coronary Disease; Coronary Vessels; Dogs; Male; Myocardium; Oxygen; Polarography